Coloduodenal fistula in right colorectal cancer: Case report and review of the literature - Hernández, Patricia Ciriano; Pinedo, Carlos Martínez; Rodríguez, Rafael Picón; Higuera, Elisa Jiménez; Peláez, Daniel Sánchez; Camuñas, Ángel Fernández; Fernández, Jesús Martín (Jour Med Resh and Health Sci, 2021)
In spite of the high incidence of colorectal cancer, cases of right colon cancer presenting with local invasion are not common. This is even more infrequent if we focus on duodenal invasion and presence of duodenal fistula. We present the case of a patient admitted to our hospital due to severe weight loss, malnutrition and bowel obstruction. The patient was diagnosed of advanced right colon cancer with coloduodenal fistula and concomitant liver metastasis. According to diagnosis, palliative surgery was performed